Effect of Apilarnil Addition to Semen Extender on Post-Thaw Sperm Quality Parameters of Rams - Koca, Recep Hakki; Gungor, Ibrahim Halil; Akarsu, Serkan Ali; Badilli, Nida; Cihangiroglu, Aslihan cakir; Acisu, Tutku Can; Gur, Seyfettin (Univ Agriculture, Fac Veterinary Science, 2024)
Apilarnil is a bee product obtained after the collection of drone larvae aged 3-7 days. It contains water, proteins, carbohydrates, fatty acids, minerals, and is rich in essential amino acids, antioxidants, as well as reproductive hormones. It contributes to the maintenance of normal metabolism due to its amino acids, vitamins, minerals, glycerophosphate calcium and folic acid contents. This study was designed to investigate the effects of different levels of apilarnil supplementation to tris-egg yolk glycerol extender on post-thaw semen quality in 6 Akkaraman rams aged around 2 years. Semen was collected by artificial vagina and diluted at 37 degrees C using five semen diluents with or without Apilarnil including 0% (Control), 0.5, 1.0, 1.5 and 2.0% apilarnil. Diluted semen was cooled to 5 degrees C; after glycerolisation and equilibration, it was frozen in liquid nitrogen, stored at -196oC and evaluated for post-thaw sperm quality. According to our results, total sperm motility, progressive sperm motility and curvi-linear velocity (VCL) values were higher in 0.5, 1.0 and 1.5% apilarnil supplemented groups compared to the control group (P<0.05). Values for sperm acrosomal damage were decreased in all apilarnil-containing groups than in the control group (P<0.05). Plasma membrane integrity was higher in the 0.5, 1.0, and 1.5% apilarnil-containing groups than in the control group (P<0.05). Malondialdehyde levels were lower in all apilarnil-treated groups compared to the control group (P<0.05). In conclusion, supplementation of apilarnil at 0.5, 1.0 and 1.5% to tris-egg yolk glycerol diluent increased sperm motility and protected plasma membrane integrity and acrosomal membrane integrity of post-thaw ram spermatozoa.
Keywords: Apilarnil; Extender; supplementation; Post Thaw; Semen quality; Ram